PENGARUH PEMASANGAN ELEKTROMAGNET PADA SISTEM BAHAN BAKAR DAN IGNITION BOOSTER PADA KABEL BUSI TERHADAP EMISI GAS BUANG CO DAN HC PADA SEPEDA MOTOR YAMAHA JUPITER Z - Triyatno, Agus (Jurnal Nosel, 2015)
The purpose of this research are: (1) Investigate the effect of installation the electromagnet on the fuel lines and the use of Ignition Booster on the spark plug wires with a variation location of the exhaust emissions gas of CO and HC on Jupiter Z motorcycles. (2) Investigate the exact value of the levels of exhaust emissions gas HC and CO on a motorcycle Jupiter-Z with the installation of the electromagnet on the fuel line, and Ignition Booster on the spark plug wires with variations location of installation. The research method used was experimental method. The research was conducted at the Laboratory of Mechanical Engineering Education Program FKIP UNS Surakarta. The tools used to measure the exhaust emissions gas of CO and HC was a gas analyzer (STARGAS 898 TYPE). The research population were a motorcycle of Yamaha Jupiter Z 2007 and the sample was motorcycle of Yamaha Jupiter Z 2007 with machine numbered 2P2675042. The Data Analysis used in this research was two-way analysis of variance. Based on the results of research were: (1) There was significant effect between the electromagnet winding wire diameter to the reduction of exhaust emissions gas CO with amount of 1.712% vol, used electromagnet winding wire diameter of 0.20 mm, while those using electromagnetic winding wire diameter of 0.30 mm amount 1.738% vol. (2) There was significant effect between the electromagnet winding wire diameter to decrease HC exhaust emissions gas with amount of 377 ppm using electromagnet winding wire diameter of 0.20 mm, while those using electromagnetic winding wire diameter of 0.30 mm amount 359.6 ppm. (3) There was significant effect between the installation of Ignition Booster to the reduction of exhaust emissions gas CO with the lowest amount of 1.529% vol, using treatment Ignition Booster installation near the spark plug. (4) There was a significant effect between the installation of Ignition Booster to the reduction of exhaust emissions gas of HC with the lowest amount of 476 ppm, using treatment Ignition Booster installation near the spark plug. (5) There was significant effect between the electromagnet winding wire diameter and location of installation Ignition Booster to the reduction of exhaust emissions gas CO with the lowest amount of 1.476% vol, using a treatment installation of winding wire diameter of 0.30 mm and Ignition Booster near the spark plug. (6) There was significant effect between the electromagnet and the winding wire diameter, location of installation Ignition Booster to the reduction of exhaust emissions gas of HC with the lowest amount of 211.3 ppm, using a treatment installation of winding wire diameter of 0.30 mm and Ignition Booster near the spark plug.